Dental hygiene : theory and practice - Darby, Michele Leonardi, 1949-; Walsh, Margaret M. (St. Louis, Mo. : Saunders/Elsevier, 2010)
From the Publisher: Comprehensive and up to date, this practical textbook offers complete coverage of today's dental hygiene skills and theories-all based on the Human Needs Model for better hygienist/patient communication. With a strong focus on clinical application, each section closely follows the critical thinking and clinical assessment approach that a hygienist must use in the classroom, clinic, and practice. Clinical competencies at the beginning of each chapter provide a clear, quick overview of exactly what you need to know, and procedure boxes with detailed steps and rationales ensure that you understand the reasoning behind each step in the competencies. In addition, new chapters on caries risk assessment and the oral-systemic health connection keep you up to date with today's major areas of research. Each section takes you from conceptual foundations of dental hygiene through patient assessment, treatment, and evaluation. Scenario boxes challenge you to integrate complex information as you assess, diagnose, plan care, and evaluate the outcome of care. Client Education Issues and Legal, Ethical and Safety Issues boxes inform you of the latest information in these important areas. Critical Thinking exercises provide opportunities for independent thought and problem solving. Tables and boxes build upon and simplify information from the text, making study and review quick and easy. Evolve website contains free online resources, including weblinks, self-assessment quizzes, and professional development worksheets for student review. A reorganized section for Individuals with Special Needs includes chapters on Cleft Palate, Physical Abuse, Blood Diseases, and Mental Illness, all reflecting evidence-based research now available in these areas. New chapters on caries risk assessment and the oral-systemic health connection-hot topics in today's dental sciences. New anesthesia guidelines keep you up to date with what's new in pain and anxiety control. Essential resources and websites are now included at the end of each chapter for easy reference. New illustrations provide a fresh, reader-friendly design. Self-assessment quizzes are available online, all case-based to follow the NBDH format. Free online access to the Legal and Ethical Decision Making chapter, including an 'asset center' to assist you with clinical skills
The dental hygiene profession / Michele Leonardi Darby, Margaret M. Walsh -- Human needs theory and dental hygiene care / Margaret M. Walsh, Michele Leonardi Darby -- Health and health promotion / Laura Lee MacDonald -- Communication and behavioral change theories / Hope E. Oliver -- Cross-cultural practice / Devan Leonardi Darby, Michele Leonardi Darby -- The dental hygiene care environment / Marie Varley Gillis -- Infection control / Eve Cuny, Helene Bednarsh, Kathy J. Eklund -- Medical emergencies / Margaret M. Walsh -- Ergonomics / Lori J. Drummer -- Personal, dental, and health histories / Frieda Atherton Pickett -- Vital signs / Cara Miyasaki -- Pharmacologic history / Ann Eshenaur Spolarich -- Extraoral and intraoral clinical assessment / Margaret J. Fehrenbach -- Assessment of the dentition / Janice Pimlott, Joan D. Leakey -- Oral hygiene assessment : soft and hard deposits / Michele Leonardi Darby, Margaret M. Walsh -- Dental caries management by risk assessment / John D. B. Featherstone -- Periodontal and risk assessment / Susan Lynn Tolle -- Impact of periodontal infections on systemic health / Gary C. Armitage -- Dental hygiene diagnosis / Michele Leonardi Darby, Margaret M. Walsh -- Dental hygiene care plan and evaluation / Karen M. Palleschi -- Toothbrushing / Joanna Asadoorian -- Mechanical oral biofilm control : interdental and supplemental self-care devices / Deborah M. Lyle -- Dentifrices / France Lavoie, Nadia Dubreuil, Louise Bourassa -- Hand-activated instruments / Michele Leonardi Darby, Margaret M. Walsh -- Ultrasonic and sonic instrumentation / Kathleen O. Hodges -- Root morphology and instrumentation implications / Marilyn Beck, Lynn Bergstrom Bryan -- Management of extrinsic and intrinsic stains / Michele Leonardi Darby, Margaret M. Walsh -- Decision making related to nonsurgical periodontal therapy / Kathleen O. Hodges -- Chemotherapy for the control of periodontal diseases / Joanna Asadoorian -- Acute gingival and periodontal conditions, lesions of endodontic origin, and avulsed teeth / Birgitta Soder -- Caries management : fluoride, chlorhexidine, xylitol, and amorphous calcium phosphate therapies / Michele Leonardi Darby -- Pit and fissure sealants / Judy Yamamoto, Maureen E. Fannon -- Nutritional counseling / Lisa F. Harper Mallonee -- Tobacco cessation / Margaret M. Walsh, Kirsten A. Jarvi -- Impressions, study casts, and oral stents / Esther K. Andrews -- Restorative therapy / Lisa Ahmann -- Behavioral management of dental fear and anxiety / Margaret M. Walsh, Michele Leonardi Darby -- Dentinal hypersensitivity management / Juliana J. Kim, Dimitrios Karastathis -- Local anesthesia / Margaret M. Walsh, Michele Leonardi Darby -- Nitrous oxide-oxygen analgesia / Margaret M. Walsh -- Persons with disabilities / Kathleen B. Muzzin -- Cardiovascular disease / Laura Mueller-Joseph -- Persons with diabetes mellitus / Deborah Bauman -- Oral care of persons with cancer / Joan M. Davis -- Persons with human immunodeficiency virus infection / Devan Leonardi Darby, Michele Leonardi Darby -- Persons with neurologic and sensory deficits / Dorothy J. Rowe, Brenda S. Kunz -- Persons with autoimmune diseases / Margaret M. Walsh -- Renal disease and organ transplantation / Cheryl Thomas -- Respiratory diseases / Joan Gugino Ellison -- Cognitively and developmentally challenged persons / Kelly M. Schultz, Michele Leonardi Darby -- Alcohol and substance abuse / Sandra Z. Zagar, Kathleen M. Schlotthauer -- Eating disorders / Laura Lee MacDonald -- Women's health and the health of their children / Maria Perno Goldie -- The older adult / Joan I. Gluch -- Persons with fixed and removable dentures / Bonnie J. Craig -- Orofacial clefts and fractured jaw / Joanna L. Harris -- Dental implant maintenance / Vivian L. Young-McDonald -- Persons with orthodontic appliances / Lee Ann Branscome Simmons -- Abuse and neglect / Inma LaCross -- Practice management / Harold A. Henson -- Career planning and professional development / Christine Hovliaras -- Legal and ethical decision making / Pamela Zarkowski
Includes bibliographical references and index
13
Keywords: Dental hygiene; Dental hygienists; Oral Health